Pressure-induced metal–insulator transition in oxygen-deficient LiNbO3-type ferroelectrics. (28th October 2021) - Xia, Chengliang; Chen, Yue; Chen, Hanghui
Abstract: Hydrostatic pressure and oxygen vacancies usually have deleterious effects on ferroelectric materials because both tend to reduce their polarization. In this work we use first-principles calculations to study an important class of ferroelectric materials—LiNbO3 -type ferroelectrics (LiNbO3 as the prototype), and find that in oxygen-deficient LiNbO3− δ, hydrostatic pressure induces an unexpected metal–insulator transition between 8 and 9 GPa. Our calculations also find that strong polar displacements persist in both metallic and insulating oxygen-deficient LiNbO3− δ and the size of polar displacements is comparable to pristine LiNbO3 under the same pressure. These properties are distinct from widely used perovskite ferroelectric oxide BaTiO3, whose polarization is quickly suppressed by hydrostatic pressure and/or oxygen vacancies. The anomalous pressure-driven metal–insulator transition in oxygen-deficient LiNbO3− δ arises from the change of an oxygen vacancy defect state. Hydrostatic pressure increases the polar displacements of oxygen-deficient LiNbO3− δ, which reduces the band width of the defect state and eventually turns it into an in-gap state. In the insulating phase, the in-gap state is further pushed away from the conduction band edge under hydrostatic pressure, which increases the fundamental gap. Our work shows that for LiNbO3 -type strong ferroelectrics, oxygen vacancies and hydrostatic pressure combined can lead to new phenomena and potential functions, in contrast to the harmful effects occurring to perovskite ferroelectric oxides such as BaTiO3 .